Kathy Acker Punk Writer (Edition 1) - Henderson, Margaret (Routledge, 2020)
This project is a feminist study of the idiosyncratic oeuvre of Kathy Acker and how her unique art and politics, located at the explosive intersection of punk, postmodernism, and feminism, critiques and exemplifies late twentieth-century capitalism.There is no female or feminist writer like Kathy Acker (and probably no male either). Her body of work-nine novels, novellas, essays, reviews, poetry, and film scripts, published in a period spanning the 1970s to the mid 1990s-is the most developed body of contemporary feminist postmodernist work and of the punk aesthetic in a literary form. Some 20 years after her death, Kathy Acker: Punk Writer gives a detailed and comprehensive analysis of how Acker melds the philosophy and poetics of the European avant-garde with the vernacular and ethos of her punk subculture to voice an idiosyncratic feminist radical politics in literary form: a punk feminism. With its aesthetics of shock, transgression, parody, Debordian détournement, caricature, and montage, her oeuvre reimagines the fin-de-siècle United States as a schlock horror film for her punk girl protagonist: Acker's cipher for herself and other rebellious and nonconformist women. This approach will allow the reader to more fully understand Acker as a writer who inhabits an explosive and creative nexus of contemporary women's writing, punk culture, and punk feminism's reimagining of late capitalism.This vital work will be an important text at both undergraduate and graduate levels in gender and women's studies, postmodern studies, and twentieth-century American literature.